Sistem Presensi Dosen Menggunakan IMEI dan GPS Smartphone dengan Data Terenkripsi - Adriana Fanggidae; Yulianto Triwahyuadi Polly (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2016)
The improvement of education quality is determined not only by student's attendance but also lecturer's attendance in class. In this paper, control system of lecturer's attendance has been developed. This system requires two types of users, which are administrator and lecturer. The administrator is responsible for data analysis and report. The lecturer confirms his/her attendance using smartphone by utilising IMEI (International Mobile Equipment Identity) and GPS (Global Positioning System). The security of the data flow in this attendance system is built using the stream cipher algorithm with three key randomization methods: odd parity Hamming code, tent map and session keys. Research finds that this contol system of lecturer's attendance is secure because of the following reasons. First, it has been built using three-tier architecture. Second, there is a security check from software system. And lastly data flow is encrypted with low correlation between plaintext and ciphertext. Furthermore, the sytem is reliable because when internet and/or GPS is lost, data between client and server is kept and is delivered once there is internet and/or GPS connection. Report of lecturer's attendance from this system is reliable and hence it is recommended to be used for lecturers' attendance report.